Atypical presentation of bilateral supplemental maxillary central incisors with unusual talon cusp - Sivakumar Nuvvula; Chaitanya Pavuluri; Abinash Mohapatra; SVSG Nirmala (Wolters Kluwer Medknow Publications, 2011)
Delayed eruption of maxillary permanent central incisors in a child poses a distressing esthetic quandary to parents, by virtue of its location in the dental architecture. Well-aligned anterior teeth add confidence to smile and have enhanced self-esteem, which is critical even in early life. Impaction of the maxillary central incisors compared to third molars or the canines is less reported; bilateral supplemental maxillary central incisors related to impacted permanent maxillary central incisors are rare and one of the supplemental central incisors showing unusual talon is still infrequent. A case of impacted maxillary permanent central incisors related to supplemental maxillary central incisors, with one of them showing an unusual talon cusp, is presented.